2010
DOI: 10.1177/070674371005500504
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mental Health of Francophone Populations in Canada, France, and Belgium: 12-Month Prevalence Rates of Common Mental Disorders (Part 1)

Abstract: Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In Canada, evidence for language-group differences in drinking habits conflicts, with studies suggesting harmful consumption among Francophones,13 greater consumption among Anglophones14 or few differences between the two 15 16. In Finland, harmful drinking patterns were more common in the Finnish-speaking majority than in the Swedish-speaking minority 17…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, evidence for language-group differences in drinking habits conflicts, with studies suggesting harmful consumption among Francophones,13 greater consumption among Anglophones14 or few differences between the two 15 16. In Finland, harmful drinking patterns were more common in the Finnish-speaking majority than in the Swedish-speaking minority 17…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Pocock 16 reported that few addictions-related prevention and treatment services are available in English for Quebec’s rural/remote OLMCs, as is also the case for Francophone OLMCs elsewhere in Canada 26,37 . Likewise, Ontario’s French-speaking OLMCs report lower rates of psychiatric admissions for addictions compared with their linguistic majority peers 24 . Also, in Manitoba, few OLMC 2S/LGBTQI+ individuals reported having used addictions-related prevention or intervention services, while nearly half indicated such services would be beneficial to them 38 .…”
Section: Results and Key Findingsmentioning
confidence: 99%
“…Previous comparisons between minority and majority Anglophone and Francophone respondents > 15 years of age using various CCHS cycles have yielded a patchwork of inconsistent results, reflecting diverse methodologies and the complexity of understanding substance use and addictions through an intersectional lens (see: Hill Collins 21,22 ). For instance, while Bouchard and Desmeules 23 report greater substance use and addictions among Francophones (both majority and minority) compared with Anglophones nationally, Tempier and collaborators 24 report the opposite trend; others report negligible or no difference between OLMCs in Canada and their majority counterparts. [25][26][27] Some regional differentials are reported, with Anglophone rural/remote OLMCs more likely to report cigarette use but less likely to report cannabis and other state-altering substances compared with their Francophone counterparts.…”
Section: Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it has been speculated that health disparities may exist between official language minority and majority groups, very little work has been done to examine this issue, specifically with regard to mental health problems. [9][10][11] Tempier and colleagues (2010) examined the 12-month prevalences for common mental disorders (major depressive episode (MDE), anxiety disorders, alcohol/substance dependence) among Quebec Francophones, outside-of-Quebec Francophones, and Canadian Anglophones (overall) using the CCHS 1.2.…”
mentioning
confidence: 99%